THE PROBLEM OF IMPLEMENTATION OF ISLAMIC EDUCATION CURRICULUM IN THE ASPECT OF MODERATION LEARNING AND HOTS EVALUATION - Hamdi, Saibatul; Wahdah, Nurul; Ahmadi, Ahmadi; Musthofa, Khabib (Nurul Jadid University, Paiton Probolinggo, East Java, 2022)
Changes and improvements to the curriculum are absolutely done by looking at the Changes and improvements to the curriculum are carried out by looking at the various needs and developments of the times. The urgency of improving this curriculum has also made the Ministry of Religion perfect the PAI curriculum as stated in KMA 183 and implementation guidelines at KMA 184 in 2019. However, it has not been fully implemented in the field like at MA Sabilal Muhtadin. The approach used in this research is qualitative with case study type. The research location is in MA Sabilal Muhtadin. Data collection techniques using interviews, observation, and documentation. While the data analysis technique using analysis according to Miles, Huberman, includes data collection, condensation, presentation, and drawing conclusions. The results showed that the main problems faced in HOTS-based moderation and evaluation learning at MA Sabilal Muhtadin were incompetent teacher resources, low levels of professionalism, and the absence of special attention from the ministry of religion regarding coaching and others at MA Sabilal Muhtadin. The implication of this research is as a material for criticism and input for madrasas and the ministry of religion to pay more attention to the preparation of the PAI curriculum implementation in madrasah.